Effect of long term treatment with azithromycin on disease parameters in cystic fibrosis: a randomised trial. Issue 3 (1st March 2002) - Wolter, J; Seeney, S; Bell, S; Bowler, S; Masel, P; McCormack, J
Abstract : Background: Relentless chronic pulmonary inflammation is the major contributor to morbidity and mortality in patients with cystic fibrosis (CF). While immunomodulating therapies such as prednisolone and ibuprofen may be beneficial, their use is limited by side effects. Macrolides have immunomodulatory properties and long term use dramatically improves prognosis in diffuse panbronchiolitis, a condition with features in common with the lung disease of CF. Methods: To determine if azithromycin (AZM) improves clinical parameters and reduces inflammation in patients with CF, a 3 month prospective randomised double blind, placebo controlled study of AZM (250 mg/day) was undertaken in adults with CF. Monthly assessment included lung function, weight, and quality of life (QOL). Blood and sputum collection assessed systemic inflammation and changes in bacterial flora. Respiratory exacerbations were treated according to the policy of the CF Unit. Results: Sixty patients were recruited (29 men) of mean (SD) age 27.9 (6.5) years and initial forced expiratory volume in 1 second (FEV1 ) 56.6 (22.3)% predicted. FEV1 % and forced vital capacity (FVC)% predicted were maintained in the AZM group while in the placebo group there was a mean (SE) decline of –3.62 (1.78)% (p=0.047) and –5.73 (1.66)% (p=0.001), respectively. Fewer courses of intravenous antibiotics were used in patients on AZM (0.37 v 1.13, p=0.016). Median C reactive protein (CRP) levels declined in the AZM group from 10 to 5.4 mg/ml but remained constant in the placebo group (p<0.001). QOL improved over time in patients on AZM and remained unchanged in those on placebo (p=0.035). Conclusion: AZM in adults with CF significantly improved QOL, reduced CRP levels and the number of respiratory exacerbations, and reduced the rate of decline in lung function. Long term AZM may have a significant impact on morbidity and mortality in patients with CF. Further studies are required to define frequency of dosing and duration of benefit.